Ru-4(mu-CO)(CO)(9)(eta(4)-mu(4)-C6H4)(eta(2)-mu(1), mu(4)-PPhCH2CH2PPh2): an unusual pyrolysis product of Ru-3(CO)(10)(dppe) containing a benzyne ligand - Diz, Enrique Lozano; Neels, Antonia; Stoeckli-Evans, Helen; Süss-Fink, Georg (My University, 2002)
The thermal decomposition of Ru-3(CO)(10)(dppe) in refluxing benzene gives, in contrast to the pyrolysis of the dppm analogue, the tetranuclear cluster Ru-4(mu-CO)(CO)(9)(eta(4)-mu(4)-C6H4) (eta(2)-mu(1), mu(4)-PCH2CH2PPh2) (1) along with Ru-3 (CO)(9)(eta(2)-mu(1), mu(2)-C6H5)(eta(3)-mu(1), mu(2)-PPhCH2CH2PPb2) (2). The single-crystal structure analysis of 1 reveals a square-planar tetraruthenium skeleton containing a eta(4)-mu(4)-benzyne ligand as well as a eta(2)-mu(1), mu(4)-phosphinidene-phosphine ligand. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: ruthenium; pyrolysis cluster; benzyne; carbonyl; phosphinidene-phosphine; RAY CRYSTAL-STRUCTURE; MOLECULAR-STRUCTURES; DISSOCIATIVE; CHEMISORPTION; ACETYLENE INCORPORATION; CLUSTER COMPLEXES; CARBONYL; CLUSTER; RUTHENIUM; PHOSPHINIDENE; DERIVATIVES; FRAMEWORK